ZnSO4.7H2O Catalyzed One-pot and Facile Synthesis of Highly Substituted Dihydro-2-oxopyrroles at Room Temperature - Mohamadpour, Farzaneh (Makara Journal of Science, 2018)
A mild and facile ZnSO4.7H2O-catalyzed procedure is developed for the convenient one-pot synthesis of highly substituted dihydro-2-oxopyrroles under mild reaction conditions. In this procedure, dihydro-2-oxopyrroles are synthesized via the four-component reactions of amines, dialkyl acetylenedicarboxylates and formaldehyde. The present procedure is an economical and mild approach that offers numerous advantages, including good to high yields, simplicity, inexpensive and readily available catalyst, and high atom economy.